Cu(II)-grafted 2D-hexagonal mesoporous material as an efficient catalyst for Sonogashira C-C cross-coupling reaction. (2021) - Paul, Luna; Chatterjee, Sauvik; Mukherjee, Sujoy; Sen, Tapas; Bhaumik, Asim
Abstract: Replacing expensive Pd-catalysts by a low cost and sustainable catalytic system is one of the major challenging areas of research in synthetic organic chemistry. Herein, we report a new Cu(II)-anchored mesoporous catalyst (SBA-NH2 -L-Cu) by immobilizing Cu(II) over organic ligand (L) anchored amino functionalized mesoporous SBA-15 (SBA-NH2 -L) material. SBA-NH2 -L-Cu has been characterized by different physicochemical techniques like powder X-ray diffraction (PXRD), Fourier-transform infrared (FTIR), high resolution transmission electron microscopy (HRTEM), N2 sorption, X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR) and thermo-gravimetric analysis (TGA). SBA-NH2 -L-Cu has been employed as an efficient heterogeneous catalyst in the Sonogashira C–C cross-coupling reaction for the synthesis of aromatic alkynes in the 1: 1 solvent mixture of 1, 4-dioxan and water in the presence of K2 CO3 base and very minor amount of Pd/C (5% on active charcoal, 0.25 mol%) as co-catalyst at 80 °C in 4 h reaction time. The catalyst is easy to handle and recycled for several times without any significant loss in catalytic activity.